Case report: Immune checkpoint inhibitor-induced paraneoplastic neurological syndrome in two patients: a case series - Shi, Guang-Qing; Lian, Heng-Ning; Wang, Huan; Xia, Jie-Qiang; Ma, Li-Jie; Zhou, Jing (Frontiers in Oncology, 2024)
Immune checkpoint inhibitors (ICIs) combined with chemotherapy have improved overall survival in patients with small-cell lung cancer, but have also led to an increase in adverse effects. The incidence of ICI-induced paraneoplastic neurological syndrome (PNS) is relatively low when the primary lung lesion is well controlled. However, it is associated with high mortality and disability rates. In this report, we present two cases of extensive-stage small-cell lung cancer with neurological symptoms and positive paraneoplastic antibodies in the serum and cerebrospinal fluid (CSF) following ICI therapy. Although the symptoms improved after treatment with systemic high-dose immunoglobulin and glucocorticoids, one patient, unfortunately, succumbed to tumor progression four months later, whereas the other patient experienced persistent difficulty in standing and walking despite improved muscle strength. In cases where neurological symptoms that cannot be explained by tumor metastases arise during ICI treatment, paraneoplastic syndromes should be considered and testing for antineuronal antibodies is crucial, as early detection and intervention can help mitigate their impact. Further research is needed to develop better predictive strategies and treatment protocols for these adverse reactions.